Process Assessment of Fencer's Parents within the scope of the Covid-19 Normalization Steps - Yusuf Barsbuğa (Türk Spor ve Egzersiz Dergisi)
The objective of this study is to measure and construe the opinions of the parents of athletes who are actively participating in competitions in our country and who are licensed by the Turkish Fencing Federation for the 2019-2020 season, regarding the organizations to be planned and the issues to be paid attention, within the scope of the Covid-19 normalization steps. The study group comprises 410 parents in total who take place on the list of licensed athlete parents of the Turkish Fencing Federation in 2019-2020.